Alveolar Macrophage Polarisation in Lung Cancer. (8th May 2014) - Almatroodi, Saleh A.; McDonald, Christine F.; Pouniotis, Dodie S.
Abstract : The role of alveolar macrophages in lung cancer is multifaceted and conflicting. Alveolar macrophage secretion of proinflammatory cytokines has been found to enhance antitumour functions, cytostasis (inhibition of tumour growth), and cytotoxicity (macrophage-mediated killing). In contrast, protumour functions of alveolar macrophages in lung cancer have also been indicated. Inhibition of antitumour function via secretion of the anti-inflammatory cytokine IL-10 as well as reduced secretion of proinflammatory cytokines and reduction of mannose receptor expression on alveolar macrophages may contribute to lung cancer progression and metastasis. Alveolar macrophages have also been found to contribute to angiogenesis and tumour growth via the secretion of IL-8 and VEGF. This paper reviews the evidence for a dual role of alveolar macrophages in lung cancer progression.